INTEGRATION OF COMMUNICATIVE ACTIVITIES IN SPEAKING CLASSES - Salimova N.A. Assistant teacher, UzSWLU Uzbekistan State World Language University (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This paper investigates the integration of communicative activities into speaking classes to enhance learners' communicative competence, fluency, and vocabulary acquisition. This study is grounded in well-established pedagogical frameworks, notably those proposed by Thornbury and Littlewood, and examines a variety of communicative tasks such as jigsaw activities, information gap exercises, role play, and mapped dialogues. The findings suggest that the importance of balancing fluency and accuracy activities and adjusting instructional strategies to the specific classroom context. The study concludes that the strategic incorporation of various communicative activities facilitates authentic language use, improves learner motivation, and promotes the development of linguistic form, grammatical accuracy and pragmatic competence in second or foreign language learners. Key words: Communicative language teaching, speaking classes, jigsaw activity, role play, information gap, fluency, accuracy.